2014
DOI: 10.1016/j.ymeth.2014.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Integrative analysis of independent transcriptome data for rare diseases

Abstract: High–throughput technologies used to interrogate transcriptomes have been generating a great amount of publicly available gene expression data. For raw diseases that lack of clinical samples and research funding, there is a practical benefit to jointly analyze existing datasets commonly related to a specific rare disease. In this study, we collected a number of independently generated transcriptome data sets from four species: Human, Fly, Mouse and Worm. All data sets included samples with both normal and abno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 50 publications
1
2
0
Order By: Relevance
“…We found that 329 mRNAs were significantly dysregulated in MELAS patients vs. controls. Interestingly, some of them were previously reported to be dysregulated in mitochondrial myopathy, including MYC, ATP2A2, ACTN3, AQP4, GLUL, TRIM63 and PFKFB3, which were partly consistent with transcriptome datasets from previous studies of mitochondrial genetic disorders 21 22 23 24 . This suggested that mitochondrial disease have disparate causes, and yet share common mechanistic themes 25 .…”
Section: Discussionsupporting
confidence: 84%
“…We found that 329 mRNAs were significantly dysregulated in MELAS patients vs. controls. Interestingly, some of them were previously reported to be dysregulated in mitochondrial myopathy, including MYC, ATP2A2, ACTN3, AQP4, GLUL, TRIM63 and PFKFB3, which were partly consistent with transcriptome datasets from previous studies of mitochondrial genetic disorders 21 22 23 24 . This suggested that mitochondrial disease have disparate causes, and yet share common mechanistic themes 25 .…”
Section: Discussionsupporting
confidence: 84%
“…Although efficacy, toxicity or optimal dose of these drugs have not been objectively assessed in human RC disease patients, they are often empirically prescribed in hopes of enhancing residual RC enzymatic function or quenching ‘toxic’ metabolites that are theorized to accumulate in RC dysfunction (Avula et al, 2014; Pfeffer et al, 2013). Provision of these therapies generally adopts a “one size fits all” approach, overtly ignoring inherent variation in RC disease subtypes, tissue-specific manifestations, and major pathogenic factors such as the predominant downstream metabolic and signaling alterations (Zhang et al, 2014; Zhang et al, 2013).…”
Section: 1 Introductionmentioning
confidence: 99%
“…Most of the studies investigating transcriptomic changes associated to mitochondrial dysfunction, however, have been carried out with microarray technologies. In fact, the only published systematic approach incorporated datasets from several organisms ( H. sapiens , M. musculus , D. melanogaster and C. elegans ) and various microarray platforms 31 .…”
Section: Discussionmentioning
confidence: 99%